Older and More Engaged: The Mediating Role of Age‐Linked Resources on Work Engagement. Issue 5 (5th August 2016) - Kim, Najung; Kang, Seung‐Wan
Abstract: In the era of a graying workforce, individuals and their employers are concerned with the impact of the graying workforce on the level of engagement at work. Contrary to the myths about older workers being less engaged, statistics have shown that the level of engagement is higher as people age. Within the broad framework of conservation of resources theory in the area of work engagement, the current study aims to clarify how older workers are more engaged at work than younger workers. Building upon socioemotional selectivity theory and continuity theory from a life‐span perspective, we explain how individuals gain more resources as they age, including the abilities to regulate emotion and to maintain a career identity. We argue that this positive relationship between age and resources explains why older people have high levels of work engagement. We tested our predictions with a sample of 613 workers in the United States. The study demonstrates that well‐regulated emotion and strong commitment to career mediate the positive relationship between age and work engagement simultaneously. These findings contribute to the understanding of an aging workforce's engagement in the workplace. © 2016 Wiley Periodicals, Inc.